(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tobacco use is a global menace and leading cause of cancers and death. Tobacco cessation strategies are being formulated world over to curb this problem. Nicotine replacement therapy (NRT) such as chewing gum, patches and inhaler and drugs like Bupropion have shown some success in smoking cessation rates in the short and long terms